Pengaruh e-WOM dan Celebrity Endorsement terhadap Minat Beli Konsumen di e-Commerce Shopee di Kota Palembang dengan Brand Image sebagai Variabel Mediasi - Indriana Hanifah; Sri Rahayu; Maftuha Nurrahmi (Training & Research Institute - Jeramba Ilmu Sukses, 2026)
This study aims to analyze the effect of celebrity endorsement, electronic word of mouth (eWOM), and brand image on consumer purchase intention in e-commerce platforms. The research method used is a quantitative approach, with data collected through questionnaires distributed to e-commerce users. The data analysis technique employed is Structural Equation Modeling (SEM) based on Partial Least Squares (PLS)with the LISREL Program. Meanwhile, electronic word of mouth (eWOM) and brand image have a positive and significant effect on consumer purchase intention. This indicates that consumers tend to rely more on online reviews and brand image rather than celebrity influence when making purchasing decisions. The implications of this study suggest that companies should focus more on managing brand image and optimizing eWOM strategies to enhance consumer purchase intention.